2000
DOI: 10.1002/(sici)1099-0518(20000101)38:1<247::aid-pola30>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of aromatic polyamides based on a bis(ether-carboxylic acid) or a dietheramine extended from 1,1-bis(4-hydroxyphenyl)-1-phenylethane

Abstract: Thermoplastic and organic‐soluble aromatic polyamides containing both bulky triphenylethane units and flexible ether linkages were prepared directly from 1,1‐bis[4‐(4‐carboxyphenoxy)phenyl]‐1‐phenylethane (III) with various aromatic diamines or from 1,1‐bis[4‐(4‐aminophenoxy)phenyl]‐1‐phenylethane (V) with various aromatic dicarboxylic diacids via triphenyl phosphite and pyridine. These polyamides had inherent viscosities ranging from 0.71 to 1.77 dL/g. All the polymers easily were dissolved in aprotic polar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Attempts to increase the solubility of polyamides have been made through the introduction of flexible units into the polymer backbone or bulky pendant groups along the main chain. [3][4][5][6][7][8][9][10][11] We have demonstrated that polyamides containing bis(phenoxy)naphthalene unit such as those from 2,7-or 1,5-bis(4-aminophenoxy)naphthalene showed enhanced solubility and comparable thermal stability as compared to conventional aramids. 12,13 However, some of these modified polyamides such as that derived from 2,7-bis(4-aminophenoxy)naphthalene (BAPON) and rigid terephthalic acid were crystalline and insoluble in organic solvents.…”
mentioning
confidence: 99%
“…Attempts to increase the solubility of polyamides have been made through the introduction of flexible units into the polymer backbone or bulky pendant groups along the main chain. [3][4][5][6][7][8][9][10][11] We have demonstrated that polyamides containing bis(phenoxy)naphthalene unit such as those from 2,7-or 1,5-bis(4-aminophenoxy)naphthalene showed enhanced solubility and comparable thermal stability as compared to conventional aramids. 12,13 However, some of these modified polyamides such as that derived from 2,7-bis(4-aminophenoxy)naphthalene (BAPON) and rigid terephthalic acid were crystalline and insoluble in organic solvents.…”
mentioning
confidence: 99%